2020
DOI: 10.1016/j.ajhg.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Signature for EZH2 Functionally Classifies Sequence Variants in Three PRC2 Complex Genes

Abstract: Weaver syndrome (WS), an overgrowth/intellectual disability syndrome (OGID), is caused by pathogenic variants in the histone methyltransferase EZH2 , which encodes a core component of the Polycomb repressive complex-2 (PRC2). Using genome-wide DNA methylation (DNAm) data for 187 individuals with OGID and 969 control subjects, we show that pathogenic variants in EZH2 generate a highly specific and sensitive DNAm signature reflecting the phenotype of WS. This signatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 54 publications
1
92
0
Order By: Relevance
“…Herein we have demonstrated that blood DNA from a patient with microcephalic dwarfism shows a similar profile to the observed for PGL patients, suggesting that a comparable activation of DNMT3A is occurring in both phenotypes. Moreover, overall alterations of DNA methylation have been also observed in blood cells from TET2 (hypermethylation) or EZH2 (hypomethylation) germline pathogenic loss-of-function variant carriers [28,29]. Thus, the methylated signature found in saliva DNA from the PGL patient described herein further supports the activating role of the new germline alteration found within the PWWP domain of DNMT3A.…”
Section: Discussionsupporting
confidence: 74%
“…Herein we have demonstrated that blood DNA from a patient with microcephalic dwarfism shows a similar profile to the observed for PGL patients, suggesting that a comparable activation of DNMT3A is occurring in both phenotypes. Moreover, overall alterations of DNA methylation have been also observed in blood cells from TET2 (hypermethylation) or EZH2 (hypomethylation) germline pathogenic loss-of-function variant carriers [28,29]. Thus, the methylated signature found in saliva DNA from the PGL patient described herein further supports the activating role of the new germline alteration found within the PWWP domain of DNMT3A.…”
Section: Discussionsupporting
confidence: 74%
“…Although the targeting of PRC2 to methylated CpGs has also been shown in vitro 59 , PRC2 typically binds to unmethylated CpG islands 60 at the promoters of inactive developmental genes. Dysfunction of PRC2 is associated with alterations of DNA methylation of CpGs in promoters of developmental genes 61 . Conversely, it has also been shown that loss of DNA methylation results in enhanced H3K27me3, suggesting that PRC2 can serve as a back-up repressive complex for newly hypomethylated CpGs.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of genome-wide methylation analysis for Mendelian neurodevelopmental disorders is that these syndromes are generally very rare. We expect that by increasing the number of samples and expanding the range and type of variants we may uncover further sub-stratification of the DNA methylation profile of FAM50A , as we have previously observed for conditions including Weaver syndrome (WVS) and Coffin–Siris syndrome (CSS) [ 8 , 17 , 40 ].…”
Section: Discussionmentioning
confidence: 79%